Obtenção de filmes a partir de mesocarpo de babaçu para liberação de extratos vegetais - CARVALHO, Liane Miranda (2019)
In this work we sought to obtain a biopolymeric film from the babassu mesocarp (MB) and apply it as a loading matrix of the hydroethanolic extract of Arrabidaea brachypoda (FAB) leaves. The mesocarp, after acid (MTA), basic (MTB) and neutral (MTN) treatment, presented characteristic bands of starchy materials (FTIR), diffraction patterns consistent with type C starches (XRD), good thermal stability (TG), as well as starch granules with more homogeneous characteristics (SEM). The films were produced by the casting method and the extract incorporated using a fixed mass of 0.015 g. After incorporation, differences in diffraction patterns were observed, with new peaks appearing at 21.91º and 34.57º, and appearance of bands at 584 and 520 cm-1 (FTIR) correlated to the presence of the extract in the matrix. Water vapor absorption tests revealed that the films exhibited less hygroscopic characteristics, maintaining constant humidity even at high relative humidity (UR), as well as low fluid absorption capacity, with values ranging from 1.77 ± 0, 15 to 1.03 ± 0.02 in phosphate buffer (PBS); from 1.99 ± 0.26 to 0.92 ± 0.03 in FCS and from 2.15 ± 0.08 to 0.99 ± 0.05 in 0.9% NaCl, and low solubility, with values around 1% solubilizable mass. Mechanical tests showed that the materials presented good tensile strength, with values ranging from 9.35 ± 0.82 to 29.16 ± 1.10 MPa. The values of ε in all cases did not exceed 4.18 ± 0.38%, showing the low elasticity of the films. Young's modules ranged from 4.00 ± 0.41 to 7.03 ± 0.07 MPa. The release assays show that the E-MTB, E-MTA and E-MTN films had a controlled release profile of FAB extract for a period of 20 h, with release rates of 7.3 ± 0.1%, 6.7 ± 0.3% and 6.2 ± 0.5% respectively. Following the HPLC / Uv-Vis (254 nm) release assay showed that all metabolites present in the extract are released into the medium. Finally, the results showed that the matrices produced showed good characteristics that indicate their potential application for controlled release of vegetable extracts.